GIS-based Selection of Appropriate Landfill Sites: The Case of Communal Grouping in Batna, Algeria - Merdassi, Abdelmoumene; Guellouh, Sami; Tebbi, Fatima Zohra; Boumezrag, Khadidja (Engineering, Technology & Applied Science Research, 2023)
The choice of a landfill site is a complex process that includes various, social, environmental, and technical, parameters which require the processing of a large amount of spatial data. The Geographic Information System (GIS), integrated with its functionalities, represents a powerful and well-adapted tool to solve this problem. This study uses the Analytic Hierarchy Process (AHP) to solve the problem of quantifying qualitative features. It enables users to make intuitive judgments about the relative eight of different predetermined criteria or options in Batna, northeastern Algeria and its neighboring municipalities. The superposition of data related to several characteristics, such as geology, hydrology, and land use, allowed us to overcome several difficulties in evaluating the location of sites suitable for establishing landfills. Results show that 88.498km2 in total meets the specified exclusion factors, of which 34.098% represent areas of very excellent suitability and 33.741% appropriate areas. Finally, low appropriateness applies to 32.161%.